Peningkatan Kreativitas User dengan MS-Word dan Canofile dalam Manajemen Dokumen Surat Masal bagi Guru dan Santri Remaja TPQ Nurul Huda Sunter Muara, Jakarta Utara - Akmaludin Akmaludin; Cepi Cahyadi; Erene Gernaria; Linda Sari Dewi; Rinawati Rinawati; Ester Arisawati; Wulan Dari (Universitas Mathla'ul Anwar Banten, 2020)
ENHANCING USER CREATIVITY WITH MS-WORD AND CANOFILE IN THE MANAGEMENT OF MASS LETTER DOCUMENTS FOR TEENAGE TEACHERS AND SANTRI OF TPQ NURUL HUDA SUNTER MUARA, JAKARTA UTARA. The conditions that are seen today, many small agencies at this time so easily become worse because of data processing constraints that are not or have not yet adapted to technological advances resulting in very rapid setbacks, because they are unable to keep up with technological trends. even middle and upper agencies can experience the same thing that will experience a downturn. Thus the implementation of this community service provides solutions for small institutions such as TPQ Nurul Huda Sunter Muara to be able to adjust to wrestling about computer technology, especially in word and database Canofile applications. Starting from the results of the free test process, it was seen that on average many did not know it, after going through this training process with high enthusiasm and enthusiasm, participants were asked to return to fill in the instrumentation in the form of a questionnaire as a barometer post test and the results were processed using the Direct Rating Method, which is processed mathematically, by using five variables and ten indicator questions. The results obtained and processed using a combination of these two applications, given good results seen from the graphic display with an average weight is 4.61 and 76.93. Thus, through computer training activities which are bridged in the form of community service, it can be said that there is an increase in good learning outcomes, although there are still psychomotor variables that must be improved, so that these psychomotor variables require routine and continuous treatment.